KUALITAS PELAYANAN PUBLIK DI DISDUKCAPIL KABUPATEN GIANYAR PADA MASA PANDEMI CORONAVIRUS DISEASE 2019 (COVID-19) - Asih, Ni Putu Giri; Wismayanti, Kadek Wiwin Dwi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2023)
During the Covid-19 pandemic, the Gianyar Regency Population and Civil Registry Office received many complaints from service users. Therefore, it is necessary to measure the quality of public services to assess the quality of public services at the Gianyar Regency Population and Civil Registry Office during the COVID-19 pandemic. This study uses a qualitative research type with a descriptive approach. This study uses the theory of service quality measurement according to Zeithaml, Berry, and Parasuraman in Hardiyansyah which includes five dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The results showed that the quality of public services at the Gianyar Regency Population and Civil Registration Service during the COVID-19 pandemic was still not running optimally. Based on the results of the study, the researcher provides recommendations, including adding support for health protocol infrastructure, increasing direct supervision of employee performance, and optimizing the provision of online services. Keywords: Public Service, Quality of Public Service, Department of Population and Civil Registry of Gianyar Regency